2022
DOI: 10.1101/2022.12.19.520916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing the evolutionary dynamics of whole-body regeneration within planarian flatworms

Abstract: Why some animals can regenerate while many others cannot remains a fascinating question. Even amongst planarian flatworms, well-known for their ability to regenerate complete animals from small body fragments, species exist that have restricted regeneration abilities or are entirely regeneration incompetent. Towards the goal of probing the evolutionary dynamics of regeneration, we have assembled a diverse live collection of planarian species from around the world. The combined quantification of species-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Unlike the planarian Schmidtea mediterranea, which regenerates a head in place of a tail after β-catenin RNAi (Gurley et al, 2008;Petersen & Reddien, 2008), M. lignano simply failed to regenerate anything. Furthermore, in planarian species that exhibit compromised anterior regeneration, β-catenin RNAi can often rescue this deficiency (Sikes & Newmark, 2013;Vila-Farré et al, 2023); however, we observed no such rescue in non-regenerative M. lignano tails (Figure S7B-C). Another key difference is observed in the expression of wnt-1.…”
Section: Discussionmentioning
confidence: 68%
“…Unlike the planarian Schmidtea mediterranea, which regenerates a head in place of a tail after β-catenin RNAi (Gurley et al, 2008;Petersen & Reddien, 2008), M. lignano simply failed to regenerate anything. Furthermore, in planarian species that exhibit compromised anterior regeneration, β-catenin RNAi can often rescue this deficiency (Sikes & Newmark, 2013;Vila-Farré et al, 2023); however, we observed no such rescue in non-regenerative M. lignano tails (Figure S7B-C). Another key difference is observed in the expression of wnt-1.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, recent findings highlighting the differential Wnt signaling activity be-1.3. STUDYING GENE REGULATORY NETWORKS IN PLANARIA tween sexual and asexual S. mediterranea, along with the enrichment of pathway components in sexual tissues, suggest the involvement of heightened Wnt signaling in sexual reproduction (Vila-Farré et al, 2023). Notably, the knockdown of beta-catenin-1 in sexual planarians resulted in the loss of vitellaria and shell glands.…”
Section: Origins Of Asexuality In Schmidtea Mediterraneamentioning
confidence: 99%
“…Additionally, a clustered heatmap of the Euclidean distances between samples was done using pheatmap function from pheatmap 1.0.12. The normalized counts of several marker genes for sexual tissues identified in the literature (Chong et al, 2011;Issigonis et al, 2022; U. W. Rouhana et al, 2017;Steiner et al, 2016;Vila-Farré et al, 2023;Y. Wang et al, 2010Zayas et al, 2005) were then assessed for each condition and compared to the asexual, ophis and egfp controls using boxplots in ggplot2.…”
Section: Differential Gene Expression Analysis Of Transcription Facto...mentioning
confidence: 99%
See 1 more Smart Citation